Survivors gihap kami coping among local first responders after Typhoon Yolanda - Alcober, Rhea C.; Nadera, Jake A.; Tiu, Ian Jim D.; Yu, Jo-Anne Glenn L. (2015)
The present study examined how first responders were able to cope after Typhoon Yolanda and came out as survivors. The research draws on qualitative data to investigate the coping strategies used by first responders. Using purposive sampling, the researchers gathered six participants for the study who fall within the age range of 25-54 years old. Semi-structured interviews were conducted to generate data and then analyzed using thematic analysis. After examining the data gathered, it was found out that first responders coped with the difficulties after the disaster through 1) getting support; 2) assuming responsibility; 3)emphasizing positive outlook; 4) going through self-discovery. On the other hand, it was also observed that detachment from the event is also an effective coping strategy.Also, coping strategies unique to first responders and the framework used have also emerged such as 1) the need to be strong for the family and 2) spirituality. Lent's Restorative Model of Well-being will be utilized to illustrate the coping of first responders in the face of disasters. Implications in using Restorative Model of Well-being in coping with disasters will be discussed.
Undergraduate thesis (B.A. Psychology)--University of the Philippines, Tacloban
Keywords: Typhoon Yolanda; Restorative Model of Well-being.